L-Serine, an Endogenous Amino Acid, Is a Potential Neuroprotective Agent for Neurological Disease and Injury - Ye, Lisha; Sun, Yechao; Jiang, Zhenglin; Wang, Guohua (Frontiers in Molecular Neuroscience, 2021)
Central nervous system (CNS) lesions are major causes of human death and disability worldwide, and they cause different extents of motor and sensory dysfunction in patients. Thus, it is crucial to develop new effective neuroprotective drugs and approaches targeted to the heterogeneous nature of CNS injury and disease. L-serine is an indispensable neurotrophic factor and a precursor for neurotransmitters. Although L-serine is a native amino acid supplement, its metabolic products have been shown to be essential not only for cell proliferation but also for neuronal development and specific functions in the brain. Growing evidence has suggested that L-serine regulates the release of several cytokines in the brain under some neuropathological conditions to recover cognitive function, improve cerebral blood flow, inhibit inflammation, promote remyelination and exert other neuroprotective effects on neurological injury. L-serine has also been used to treat epilepsy, schizophrenia, psychosis, and Alzheimer’s Disease as well as other neurological diseases. Furthermore, the dosing of animals with L-serine and human clinical trials investigating the therapeutic effects of L-serine generally support the safety of L-serine. The high significance of this review lies in its emphasis on the therapeutic potential of using L-serine as a general treatment for numerous CNS diseases and injuries. Because L-serine performs a broad spectrum of functions, it may be clinically used as an effective neuroprotective agent.